Why are median phosphorus concentrations improving in New Zealand streams and rivers?. Issue 2 (3rd April 2019) - McDowell, Richard W.; Hedley, Mike J.; Pletnyakov, Peter; Rissmann, Clint; Catto, Warwick; Patrick, Wes
ABSTRACT: The enrichment of phosphorus (P) in streams and rivers can impair water quality, but concentrations have decreased. We found little evidence that this improvement was caused by a decrease in soil Olsen P concentrations or imported P (e.g. fertiliser), a change to low water-soluble P fertilisers, or that greater nitrate loads were assimilating P from groundwater or sediments. Possible causes of improvement were that land use change had decreased erosion, more nitrogen fertiliser use was assimilating soil P, and a greater awareness of P as an environmental issue. However, the most probable causes were that strategies were mitigating P loss from land, guidelines were directing where to best use strategies, and policy instruments were including P management. These findings support the development and implementation of mitigations, supported by voluntary guidelines and regulation. However, our findings can be strengthened if data are referenced to equivalent, and finer spatial and temporal scales.